Isolated mediotegmental lesion causing narcolepsy and rapid eye movement sleep behaviour disorder: a case evidencing a common pathway in narcolepsy and rapid eye movement sleep behaviour disorder. Issue 4 (16th March 2007) - Mathis, J; Hess, C W; Bassetti, C
Abstract : Narcolepsy is usually an idiopathic disorder, often with a genetic predisposition. Symptomatic cases have been described repeatedly, often as a consequence of hypothalamic lesions. Conversely, REM (rapid eye movement) sleep behaviour disorder (RBD) is usually a secondary disorder, often due to degenerative brain stem disorders or narcolepsy. The case of a hitherto healthy man is presented, who simultaneously developed narcolepsy and RBD as the result of an acute focal inflammatory lesion in the dorsomedial pontine tegmentum in the presence of normal cerebrospinal fluid hypocretin-1 levels and in the absence of human lymphocyte antigen haplotypes typically associated with narcolepsy and RBD (DQB1*0602, DQB1*05). This first observation of symptomatic narcolepsy with RBD underlines the importance of the mediotegmental pontine area in the pathophysiology of both disorders, even in the absence of a detectable hypocretin deficiency and a genetic predisposition.